Metataxonomics study of dental bioaerosols affected by waterline disinfection - Wachirakorn Poolkerd; Boonlased Swatasuk; Methanee Saengpitak; Sureeporn Muangsawat; Piriya Klankeo; Kittisak Thotsaporn; Ruchanee Salingcarnboriboon Ampornaramveth (BMC Oral Health)
Abstract Background Microorganisms in dental unit water (DUW) play a significant role in dental bioaerosols. If the methods used to decontaminate DUW also help improve air quality in dental clinics is worth exploring. In this study, we aim to identify the source of bacteria in dental bioaerosols and investigate the impact of waterline disinfectants on the quantity and composition of bacteria in DUW and bioaerosols. Methods Two dental chair units in a separate treatment room are installed with two different waterline decontamination systems, a plasma or iodine cartridge. The experiment was performed in two phases, before and after installing the decontamination systems. Aerosol is generated via running airotor in the subject’s mouth. Before and after the procedure, the air samples were collected with an active air sampling machine onto agar plate and filter paper for genomic DNA extraction. The subject’s saliva and DUW samples were also collected. The samples were analyzed further with bacterial counting and metataxonomics analysis. Results The bacteria present in the air sample after the aerosol-generating procedure were confirmed to be derived from the air-before, saliva, and DUW in 51.43%, 6.38%, and 18.60%, respectively. The saliva samples demonstrated the highest alpha diversity (within the sample), whereas the air samples had the least. Both waterline disinfectants effectively controlled bacteria in DUW but did not affect the bacterial number and composition in the air. Conclusions Dental bioaerosols are composed of bacteria from saliva and DUW. Plasma and iodine showed a trend in controlling bacterial contamination in DUW but did not alter the bacterial count and composition in dental bioaerosols.